From Ephrem to Romanos: Interactions between Syriac and Greek in Late Antiquity - Healey, John F. (Journal of Semitic studies, 2002)
From Ephrem to Romanos: Interactions between Syriac and Greek in Late Antiquity SebastianBrock (Variorum Collected Studies Series CS644). Ashgate PublishingAldershot 1999x + 340Hardback£55.00 0‐86078‐800‐8 , 1University of Manchester